BIM Use by Architecture, Engineering, and Construction (AEC) Industry in Educational Facility Projects - Cristina Moreno; Svetlana Olbina; Raja R. Issa (Advances in Civil Engineering)
In recent years, many public and private sector owners have started to require a building information modeling (BIM) component in new construction projects. Although there has been a significant increase in industry-wide acceptance of BIM, it is still not a standard practice in the educational facility sector. This research aimed at exploring the use of BIM in educational facility projects by the architecture, engineering, and construction (AEC) disciplines. A survey that investigated BIM adoption at the company level, BIM implementation in projects, benefits of using BIM, and obstacles to using BIM was distributed to architects, site engineers, structural engineers, mechanical engineers, and contractors across the United States. The survey results showed that a majority of the respondents from all five disciplines used BIM. BIM was most commonly used for 3D visualization, automation of documentation, and clash detection. The most important benefits of BIM included better marketing and clearer understanding of projects which is crucial for clients such as school students, teachers, and principals. Lack of expertise and need for training seemed to be main obstacles to BIM use. The research contributes to the body of knowledge by showing prevalence of BIM use on educational facility projects and indicating how BIM could help improve collaborative knowledge sharing among designers, contractors, and clients, resulting in better quality educational buildings. These research findings can be used to assist AEC companies that are interested in implementing BIM in the educational facility projects.